EFICIENCIA DE FUNGICIDAS AZUFRADOS EN EL CONTROL DE SIGATOKA NEGRA (Pseudocercospora fijiensis M.) EN BANANO (Musa x paradisiaca) - Siavichay Franco, Juan Carlos (2023)
This research evaluated the efficiency of different sulfur fungicides at low pressure for the control of black sigatoka (Pseudocercospora fijiensis) in banana (Musa paradisiaca). The experiment was carried out in the experimental plots of BASF Ecuador, located on the "La María" campus of the State Technical University of Quevedo. The methodology used was that of Stover modified by Gauhl, which allows determining the percentage of infection.